The politics of electricity planning in South Africa: A review of dominant advocacy coalitions seeking to influence the Integrated Resource Plan of 2010 (IRP2010), and its update in 2013 - Martin, Brenda (Energy Research Centre, 2017)
There are two policy events that are the focus of the research: the Integrated Resource Plan of 2010 (IRP2010), and its 2013 update report. The research is mainly concerned with the political influence exerted by the identified advocacy coalitions and the political context they acted within, during the period under review: June 2010 to June 2015. The research and the analysis of findings has been guided by the Advocacy Coalitions Framework (ACF) theory. In keeping with ACF methodology, the research is based on an understanding of the preceding 10 to 15 years in order to better interpret current unfolding policy events, identify the coalitions and their activities, and ultimately present key findings that are based on empirical evidence. The narrative seeks to take account of parallel unfolding dimensions which collectively portray a noteworthy tapestry: coalition beliefs and activities, and policy events within the SA electricity supply sector over time. By the final chapter, it should be clear who exerted influence, what their dominant advocacy issues were, whether such influence was evident in policy that was promulgated, and what changed along the way. Empirical findings provide answers to the following research questions: 1. From the IRP2010 to its 2013 Update report, which were the dominant coalitions seeking to influence planning? 2. What were the dominant advocacy issues raised by these coalitions? 3. What evidence could be found for how the issues of dominant advocacy coalitions were realised in electricity policy? 4. What can be concluded and what are the implications for future electricity planning? The dissertation begins with a brief introduction of what the theoretical framework ACF would consider the energy policy system i.e. the international and the national energy and electricity governance context. ACF is then applied to understand the politics of electricity planning in South Africa, two dominant advocacy coalitions active within that sub-system, and their advocated beliefs, in order to answer the first two research questions. Chapter 5 and 6 together answer research question three. In chapter 5, ACF is applied to understand process and outcomes for the IRP2010 as promulgated. Chapter 6 considers the process and outcomes related to the IRP's 2013 update report which is not recognised in policy, and describes some of the shifts that occurred within and between coalitions and within the electricity policy sub-system by June 2015. The picture that emerges is that of an electricity sector within a new democracy that has sought to move beyond its apartheid-era policy legacies and has become characterised by decision-making based on politics rather than evidence. In answering the fourth question it is concluded that recent decision-making and planning processes in South Africa's electricity sector have undergone distinct periods of open and closed consultative process. There has been a steady opening up of process particularly during the policy period up to December 2010. From 2011 onward, a closing down of process has steadily been underway, particularly in relation to the IRP2013 update report. This has occurred at the same time as broad public support for transparent decision-making that is based on evidence had grown. While the analysis focuses on issues of ideological belief, politics and process, rather than on technology and economics, two distinct and contested electricity supply investment options related to power sector reform have dominated the advocacy beliefs and actions of the two coalitions reviewed, as well as the policy choices made by government: nuclear power on the one hand, and renewable energy on the other. These supply options and some of the issues of political economy associated with them are considered in the latter parts of the dissertation. A summary of the main findings Two high-level coalitions have dominated the IRP2010 process and its 2013 update: one favouring orthodox solutions to power supply, and the other favouring transition to a reformed power sector. The coalitions are: a. The Orthodox coalition: enjoying both greater political support for and capacity to influence the achievement of conventional economic growth. Their advocacy tended to focus on past experience and retaining the power supply status quo. b. The Reform coalition: less politically influential, and enjoying less political support. Their advocacy tended toward learning from past experience and changing the status quo. Among the issues which the two coalitions differ on, the five most contested issues were: tariffs and investment, power sector reform, climate change, nuclear power, and renewable energy. The promulgated electricity plan reflects wins and losses to both coalitions. For the IRP2010, more evidence was found of policy 'wins' for the Orthodox coalition. For the 2013 update report, more evidence was found of policy 'wins' for the Reform coalition, Nevertheless, given that the 2013 update report is not recognised in policy, it is concluded that the Orthodox coalition has been more influential in its advocacy. For the IRP 2013 update report, analysis of policy wins and losses became more complex, with alliances shifting within and between the two coalitions under review. Evidence has been found of an initial steady opening up of public consultation process in the decade preceding 2010, which later closed down steadily by June 2015. The closing down of process has been most evident to those involved in electricity planning, since mid-2010.The influential role of the Presidency, on the nuclear investment decision is perceived by electricity planning stakeholders to have begun in June 2010. The clear political support for nuclear procurement has resulted in greater unified advocacy against nuclear power, and lesser advocacy against renewable energy. The continued non-recognition of the IRP2013 update report in policy has benefited both wind power investment and new nuclear power procurement. Ultimately, the delay in the promulgation of a well-regarded, technically robust updated IRP threatens confidence in electricity planning process and is perceived by senior electricity actors to be entrenching a situation where politics is currently playing a more influential role than evidence, in South Africa's electricity planning.